Problems and Improvement Methods of the Layout of Urban Rail Transit Feeder Transportation Facilities - ZHENG Xiang; NONG Xingzhong; WANG Zhi; QIN Yuan; YE Xiafei (Chengshi guidao jiaotong yanjiu)
[Objective] The collection and distribution capacity of urban rail transit is often closely related to the characteristics and capabilities of feeder transportation means. The advantages of urban rail transit will be fully realized only when urban rail transit and its supporting feeder transportation operate in coordination. Therefore, it is necessary to study the layout issue of urban rail transit feeder transportation facilities and their improvement methods. [Method] The main feeder transportation modes and their facilities at urban rail transit stations are summarized. Based on typical urban cases at home and abroad, factors such as differences in alternative options and weather are comprehensively considered, to construct an optimized model for estimating the passenger flow demand of feeder transportation and the optimized one for calculating the scale of feeder transportation mode facilities. The priority and configuration principles for the allocation of feeder transportation facilities are proposed. [Result & Conclusion] The peak demand period for parking facilities of the feeder transportation mode using passengers′ own vehicles is generally in the afternoon. When calculating the scale of parking lots in this scenario, the peak parking value should be used as the calculation basis. For the two feeder modes of private bicycles and park-and-ride, the indicator of non-transfer parking rate can reflect the situation where bicycle parking and private car parking lots serving the transfer at urban rail transit stations are occupied by non-urban rail transit passengers during use. Lowering this indicator plays a positive role in reducing the unwillingness of urban rail transit passengers to choose urban rail travel due to insufficient parking lots.